2019
DOI: 10.1073/pnas.1821116116
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2A has an essential role in promoting thymocyte survival during selection

Abstract: The development of thymocytes to mature T cells in the thymus is tightly controlled by cellular selection, in which only a small fraction of thymocytes equipped with proper quality of TCRs progress to maturation. It is pivotal to protect the survival of the few T cells, which pass the selection. However, the signaling events, which safeguard the cell survival in thymus, are not totally understood. In this study, protein Ser/Thr phosphorylation in thymocytes undergoing positive selection is profiled by mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…To elucidate the function of SRSF1 in the late stage of thymocyte development, we crossed Srsf1 fl/fl mice (18) with Lck-Cre mice (19), which drives the Cre recombinase expression by proximal Lck promoter (20) and effectively deletes the floxed gene fragment at the DP stage (21,22), to conditionally inactivate SRSF1 (Fig. 1A).…”
Section: Srsf1 Plays Critical Roles In the Late Stage Of Thymocyte De...mentioning
confidence: 99%
“…To elucidate the function of SRSF1 in the late stage of thymocyte development, we crossed Srsf1 fl/fl mice (18) with Lck-Cre mice (19), which drives the Cre recombinase expression by proximal Lck promoter (20) and effectively deletes the floxed gene fragment at the DP stage (21,22), to conditionally inactivate SRSF1 (Fig. 1A).…”
Section: Srsf1 Plays Critical Roles In the Late Stage Of Thymocyte De...mentioning
confidence: 99%
“…Bioinformatics analysis is essential for analyzing the large amounts of data generated by sequencing platforms. Bioinformatic analysis of miRNAs and mRNAs microarray profiling showed that miR‐203 targeting protein phosphatase 2A catalytic subunit α (ppp2ca) aggravated seizure activity at 24 hours and 28 days in the pilocarpine‐induced mouse model, 63 but further functional studies are needed to confirm their relationship. De novo mutations of ppp2ca highlight its importance in neurodevelopmental disorders 64 .…”
Section: Mir‐203mentioning
confidence: 99%
“…Statistical analysis showed that 1474 genes were expressed differentially, including 623 upregulated genes and 851 downregulated genes with a log 2 fold change of ≥ 1.2 (Fig. 6a) [45]. The regulated genes with a log2 fold change of ≥ 4 between Nc-1 and ΔNcACBP strains are provided in Additional file 1: Table S2.…”
Section: Loss Of Ncacbp Results In Global Changes In the Expression Omentioning
confidence: 99%